PROCESSAMENTO E CARACTERIZAÇÃO DE COMPÓSITOS SUPERCONDUTORES YBa2Cu3O7-d/ Ag - Azambuja, Paula de (2008)
In this work is presented an experimental study on the effects of the addition of Ag to the system YBa2Cu3O7-d. The silver can be added to the YBa2Cu3O7-d system through the mixture with metallic Ag, with oxide of silver (Ag2O) or with nitrate of silver (AgNO3), using different techniques and forms of processing. The addition of silver to the YBa2Cu3O7-d system is known by minimizing the properties undesirable of the system, without deleterious effects in superconducting properties. She is responsible for the significant increase in the conductivity thermal and electric of the system; it improves of the mechanical properties, as the resistance of fracture and elasticity of the material, from the reduction of the porosity; it reduces the weak links between the superconducting grains, improving the contact between the same. The samples used in this work had been processed for different experimental routes: in the first set of samples Ag2O was added to the YBa2Cu3O7-d system previously prepared; on the second set of samples the silver oxide was mixed to the precursors Y2O3, BaCO3 and CuO and then the YBa2Cu3O7-d system was processed; and in the third set of samples metallic silver was added to the YBa2Cu3O7-d system previously prepared. The characterization of the samples, pure and doped with silver, was realized through with aid of different techniques enclosing: analysis of the crystalline structure; analysis of the superficial topology; measures calorimetric; mechanical properties; properties of electronic transport and magnetic properties. The obtained results are coherent with results of other works on composites YBa2Cu3O7-d/Ag and demonstrate that the addition of the silver to the YBa2Cu3O7-d system, of a general form, improves the properties of this system. Key Words: Superconductivity; YBa2Cu3O7-d system; processing of composites YBa2Cu3O7-d/ Ag; characterization of materials.